Estudio de la cobertura vegetal del páramo de San Marcos. Ecuador-2011 - Bermeo Hurtado, Dexi Cecilia (2012)
This research was conducted in the National Park Cayambe - Coca in order to understand and evaluate the current state of the vegetation of the different ecosystems that are distributed in provinces of Pichincha and Sucumbíos in northern Ecuador, to be affected by the implementation of infrastructure projects for implementation of irrigation (Irrigation Canal Cayambe Pedro Moncayo), through the implementation of 17 permanent transects that were located in the most representative of the field of study with a distance of 100 m points sampled every 5 m with an area of 4 square meters, thus able to determine several natural formations among which we identified the moor herbaceous, shrubby, evergreen cushion and upper montage forest, we proceeded to perform calculations of diversity indices of Simpson and Shannon flora, georeferenced and placed on a map of the zone.